2020
DOI: 10.3389/fpsyg.2020.00869
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Medical and Nursing Managers’ Perspectives on Health-Related Work Design Interventions. A Qualitative Study

Abstract: Background: Research indicates that the active support of managers is essential for the sustainable implementation of health-related work design interventions in organizations. However, little is known about managers' perceptions of such health promotion measures. Objective: Our study aims to provide information that help to foster managers active support of health-related work design interventions in hospitals. Based on Ajzen's Theory of Planned Behavior (TPB) we explore the attitudes, perceived organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 70 publications
1
38
0
3
Order By: Relevance
“…This view is corroborated by a recently published study [ 28 ] that showed that managers perceive decision latitude more at the individual and team level (e.g., through appraisal interviews, designing a fair work plan) and less at the organizational level. Various system-related reasons are cited by managers for not being able to create better working conditions by their own efforts through health-promoting work organization.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This view is corroborated by a recently published study [ 28 ] that showed that managers perceive decision latitude more at the individual and team level (e.g., through appraisal interviews, designing a fair work plan) and less at the organizational level. Various system-related reasons are cited by managers for not being able to create better working conditions by their own efforts through health-promoting work organization.…”
Section: Discussionsupporting
confidence: 58%
“…Various system-related reasons are cited by managers for not being able to create better working conditions by their own efforts through health-promoting work organization. In particular, for economic reasons in some cases, they feel externally determined by the top hospital management or the nursing service management and restricted in their work autonomy [ 28 ]. Since a health-related work design is very effective for economic success and for the quality of treatment, Genrich et al [ 28 ] suggest that clear organizational norms and goals should be established in hospitals and that the health promotion of employees is an important organizational goal [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore seems more relevant to look at the PSC than at the level of social support alone. In addition, a recent study suggested that medical and nursing managers in hospitals themselves need to get more work-design competencies and decision latitude to get more control and to be able to sufficiently counteract stress factors [ 59 ]. We therefore propose for future research to investigate how the PSC influences the perception of the managers.…”
Section: Discussionmentioning
confidence: 99%
“…Die Befragten beschrieben Maßnahmen der Selbstfürsorge wie gesunde Ernährung, Sport, Entspannungstechniken und ausreichend Schlaf sowie Rückzugsmöglichkeiten am Arbeitsplatz, emotionale Unterstützung durch den Austausch mit Kolleginnen, familiäre Beziehungen und spirituelle Kraftquellen als wesentlich [11]. Eine qualitative Studie zur Perspektive von Führungskräften auf die Reduzierung von Arbeitsbelastungen im Krankenhaus zeigte, dass diese vorwiegend auf der individuellen-und teambezogenen Ebene gesehen werden, beispielsweise in Form von Mitarbeitergesprächen und sozialer Unterstützung [12].…”
Section: Introductionunclassified